Changing human-ecological relationships and drivers using the Quesungual agroforestry system in western Honduras - Ayarza, Miguel Angel; Huber-Sannwald, E.; Herrick, Jeffrey E.; Reynolds, J.F.; García Barrios, L.; Welchez, L.A.; Lentes, P.; Pavon, Jellin; Morales, J. (Cambridge University Press, 2010)
Development of sustainable agricultural production systems in the tropics is challenging in part because the local and external conditions that affect sustainability are constantly in flux. The Quesungual agroforestry system (QSMAS) was developed in response to these changing conditions. The history and potential future of the QSMAS provide an opportunity to consider the factors affecting small-scale agricultural production systems on marginal lands throughout the world. We evaluated the QSMAS in Honduras in the context of the five principles of the Drylands Development Paradigm (DDP) during three periods: pre-QSMAS, QSMAS adoption and the future. The first two periods provided lessons that could be relevant to other regions. The QSMAS system in Honduras must continue to evolve, if long-term benefits are to be realized. We conclude that while the DDP was a useful framework for systematically identifying the critical drivers and processes determining the sustainability of QSMAS in Honduras, it is ultimately no more able to predict the future than the collective knowledge of those who choose to apply it. The DDP, however, can facilitate the integration and application of knowledge.